2011
DOI: 10.3923/ijps.2011.160.168
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Novel Microbial 6-Phytase Expressed in Aspergillus oryzae on the Performance and Phosphorus Utilization in Broiler Chickens

Abstract: The efficacy and safety of a novel microbial 6-phytase expressed via the use of synthetic genes in Aspergillus oryzae was investigated from d 8 to 22 of age using 480 Ross PM3 broiler chickens. Five treatments were tested. A diet containing 5.6 g/kg of Phosphorus (P) was fed to the control treatment. Another diet containing 4.1 g/kg P was fed to another treatment as negative control. This diet was fed in 3 other treatments with the addition of phytase (500, 1000, or 2000 U/kg). Feed intake, body weight, tibia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…The results indicated that the use of phosphorus‐deficient diet reduced BWG as reflected on FCR and other performance parameters in broiler chickens. The findings are consistent with those in the previous studies (Aureli et al, 2011; Ravindran, Cowieson, & Selle, 2008; Rutherfurd, Chung, Thomas, Zou, & Moughan, 2012). Phosphorus is an essential mineral in chickens and plays the main role in bone strength and cellular metabolism, as a part of the energy currency of the cell.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results indicated that the use of phosphorus‐deficient diet reduced BWG as reflected on FCR and other performance parameters in broiler chickens. The findings are consistent with those in the previous studies (Aureli et al, 2011; Ravindran, Cowieson, & Selle, 2008; Rutherfurd, Chung, Thomas, Zou, & Moughan, 2012). Phosphorus is an essential mineral in chickens and plays the main role in bone strength and cellular metabolism, as a part of the energy currency of the cell.…”
Section: Discussionsupporting
confidence: 93%
“…It seems that the application of L. salivarius , together with RLL in the deficient diet, can enhance BWG, similar to those of PC and commercial phytase. In addition, a reduction in the amount of available phosphorus in the diet decreases feed intake and the addition of phytase can compensate for the negative impact on feed intake (Aureli et al, 2011; Ravindran et al, 2008). However, no reduction of feed intake occurred in the present study, which may be related to the fact that the deficient diet is fed to the chickens at seven days of age, and the birds are fed with a standard diet during this time, which may increase phosphorus reserves in the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this there are a huge amount of in vivo studies demonstrating that phytases effectively releases phosphate in animals fed diets containing SBM e.g. Aureli et al [70] showing phytase efficacy in broilers.…”
Section: Phytic Acid Degrading Enzymesmentioning
confidence: 91%
“…The respective negative control diet was formulated with moderate deficiency of phosphorus and Ca and fed as such (negative control, NC) or supplemented with 2.0 g/kg non‐phytate‐P from dicalcium phosphate dihydrate (DCP) as a positive control (PC). NC was supplemented with bacterial 6‐phytase from Citrobacter braakii (DSM Nutritional Products Ltd, Kaiseraugst, Switzerland) at 1000 U/kg (Phy1000) (one unit (U) of phytase is defined as the activity that releases 1 μ mol inorganic phosphate from 5.0 m m phytate per minute at pH 5.5 and 37 °C) (Aureli et al., ). Activity of phytase in the diet was determined using the ISO 30024:2009 methodology entitled: Animal feeding stuffs – Determination of phytase activity.…”
Section: Methodsmentioning
confidence: 99%